Effect of oral administration of efficient microorganisms on productive indicators, diarrheal syndrome and blood count in suckling pigs - Carvajal, María C.; Aroche, R.; Castro, E.; León, María R.; Guilarte, J.; Rodríguez, R.; Martínez, Y. (Cuban Journal of Agricultural Science, 2021)
In order to evaluate the effect of oral administration of efficient microorganisms on the productive indicators, diarrheal syndrome and blood count in suckling pigs, an experiment with 20 piglets, one day old (1.83 ± 0.31 kg of live weight) was developed, in the enterprise Cría Pedregales, belonging to Empresa Porcina Granma, Cuba. Two treatments were established: T1) basal diet and T2) oral supply of 5 mL of efficient microorganisms for seven consecutive days, from 24 h after born and after ingestion of colostrums. The addition of efficient microorganisms significantly increased the mean daily gain in the periods 7-14, 14-21 and 1-21 days of life (P <0.05) and decreased the incidence of diarrhea by 2.86 % during the 21 days of the study (P <0.05). In addition, this additive did not affect the blood indicators of pigs (P> 0.05), and all the animals showed normal parameters for this pig category. Oral administration of 5 mL with efficient microorganisms (GERMEVIT) is recommended during the first seven days of life to improve productive indicators and reduce the presence of diarrhea, without modifying the blood count of suckling pigs. Key words: microbial additive, suckling piglet, diarrhea, hematological parameter, productivity